SPEED TOOL INNOVATION FOR ROUTINE MAINTENANCE OF PERSONAL PROTECTIVE EQUIPMENT - M. Fadli Fadli; Thursina Handayani (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2026)
Personal Protective Equipment (PPE) is critical for Airport Rescue and Fire Fighting (ARFF) personnel, yet its maintenance—particularly drying—remains manual and weather-dependent, creating risks of microbial growth and reduced protective effectiveness. This study developed the SPEED device (Effective, Efficient, and Powerful PPE Drying System) using a Research and Development (R&D) approach with the ADDIE model. Data were collected through observation, interviews, and expert validation at the ARFF Unit of Yogyakarta International Airport. SPEED integrates a heating element, exhaust fan, and UV-C lamp (344 W total) with automatic temperature and timer control. Expert validation by three ARFF practitioners and one academic validator yielded a score of 100% (